Gastric neuroendocrine tumour in a female with Turner syndrome – a case report - Kula, Zbigniew; Zegarski, Wojciech; Weishof, Alicja (Contemporary Oncology/Współczesna Onkologia, 2008)
We report an extremely rare case of a 38-year-old female with Turner syndrome and gastric neuroendocrine tumour. In the clinical picture symptoms of anaemia dominated. During gastroscopy numerous small polyps of the body and fundus of the stomach were recognized. A diagnosis of Turner syndrome was made on the basis of the presence of chromosomal abnormality and ovarian failure. She was operated on the suspicion of gastric carcinoma. The final diagnosis was well-differentiated endocrine tumour (type I gastric carcinoid). On the basis of this case, we report the association of Turner syndrome with malignancies and also some aspects of gastric neuroendocrine tumours.